2013
DOI: 10.1158/1078-0432.ccr-12-3202
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Signal–Regulated Kinase 5: A Potential Therapeutic Target for Malignant Mesotheliomas

Abstract: Purpose Malignant mesothelioma (MM) is a devastating disease with a need for new treatment strategies. In the present study we demonstrated the importance of ERK5 in MM tumor growth and treatment. Experimental Design ERK5 as a target for MM therapy was verified using mesothelial and mesothelioma cell lines as well as by xenograft SCID mouse models. Results We first showed that crocidolite asbestos activated ERK5 in LP9 cells and mesothelioma cell lines exhibit constitutive activation of ERK5. Addition of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(61 citation statements)
references
References 44 publications
4
55
2
Order By: Relevance
“…Recent studies from our lab also show that chemotherapeutic drugs such as doxorubicin (Dox) can activate ERKs (11). Moreover, inhibition of various ERKs can attenuate MM tumor growth in SCID mice (11)(12)(13).…”
Section: Clinical Relevancementioning
confidence: 96%
See 3 more Smart Citations
“…Recent studies from our lab also show that chemotherapeutic drugs such as doxorubicin (Dox) can activate ERKs (11). Moreover, inhibition of various ERKs can attenuate MM tumor growth in SCID mice (11)(12)(13).…”
Section: Clinical Relevancementioning
confidence: 96%
“…In human MMs, ERK5 is constitutively activated and further elevated by Dox, and ERK5 silencing attenuates invasion of MMs in vitro and reduction of MM growth (12). Moreover, crocidolite asbestos fibers, the most potent asbestos type in the causation of MM, cause protracted activation of ERK1/2 and ERK5 via EGFR-dependent versus independent pathways in rodent mesothelial and lung epithelial cells (1,17).…”
Section: Clinical Relevancementioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular signal-regulated kinase (ERK) 5 is the least studied member of the mitogen-activated protein kinase (MAPK) family, and is implicated in important cellular processes, including gene expression, proliferation, apoptosis, angiogenesis, cell motility and differentiation (15)(16)(17)(18) (19)(20)(21) and triggers a motility and invasive phenotype of cells (22)(23)(24). Additional studies have suggested a differential regulatory role of ERK5 in EMT (25,26).…”
Section: Introductionmentioning
confidence: 99%